2022
DOI: 10.3389/fmicb.2022.931440
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effects of Dietary Pesticides on the Gut Microbiome and Neurodevelopment

Abstract: Many agricultural pesticides include substances that are known to be harmful to human health and while some have been banned from developed countries, they are still being used in developing countries such as Brazil. Recent studies have shown that low-level chronic dietary exposure to pesticides can affect the human gut microbiota. This possible hazardous effect of pesticides on human health has not been specifically recognized by government regulatory agencies. In Brazil, for instance, of the 10 best-selling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that organophosphate pesticides including DDVP can suppress appetite and reduce weight gain in animal models [55] . Recent studies have demonstrated disruption of the gut microbiome, capable of producing changes in gut barrier function and intestinal motility following pesticides exposure [1] , [110] , [116] , [41] , [80] . These changes can drive reduced food and water intake, as well as changes in body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that organophosphate pesticides including DDVP can suppress appetite and reduce weight gain in animal models [55] . Recent studies have demonstrated disruption of the gut microbiome, capable of producing changes in gut barrier function and intestinal motility following pesticides exposure [1] , [110] , [116] , [41] , [80] . These changes can drive reduced food and water intake, as well as changes in body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Even at maximum residue levels tolerated by the European Commission and United States Department of Agriculture, pesticides have been demonstrated to alter the composition of the gut microbiome in both humans and animals [80]. Similar to dietary impacts on the gut microbiome, chronic exposure to pesticides, such as those containing arsenic, appears to drastically change the composition and metabolism of the gut microbial populations [81].…”
Section: Effect Of Diet and Environmental Factors On The Microbiomementioning
confidence: 99%
“…However, in recent years, there has been growing attention to the potential long-term health effects of prolonged exposure to pesticides. 4,7 Although pesticides typically undergo testing and evaluation for acute human health effects before being brought to market, research indicates that long-term exposure to certain pesticides may lead to a variety of health issues, including endocrine disruption, 8,9 liver damage, 10,11 intestinal inflammation, 12,13 and translocation of the gut bacterial, which is considered a novel target for human health. 14,15 As a result, modern pesticide risk assessments have begun to consider not only the acute toxicity but also the longterm health implications of pesticide exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides play a crucial role in agricultural production, serving primarily to prevent and control various diseases, pests, and weeds. , However, due to their widespread use, pesticide residues can potentially enter mammals, including humans, through the food chain and accumulate within their bodies, posing health risks. , Therefore, assessing the impact of pesticide exposure on mammalian, and particularly, human health remains a subject of ongoing concern. , Traditionally, pesticide risk assessments have focused primarily on acute toxicity. However, in recent years, there has been growing attention to the potential long-term health effects of prolonged exposure to pesticides. , Although pesticides typically undergo testing and evaluation for acute human health effects before being brought to market, research indicates that long-term exposure to certain pesticides may lead to a variety of health issues, including endocrine disruption, , liver damage, , intestinal inflammation, , and translocation of the gut bacterial, which is considered a novel target for human health. , As a result, modern pesticide risk assessments have begun to consider not only the acute toxicity but also the long-term health implications of pesticide exposure.…”
Section: Introductionmentioning
confidence: 99%